Headlines in history the 1100s - Cothran, Helen (Headlines in history, 2001)
Divided into geographical areas, this book explores the challenges civilizations faced in the 1100s, focusing on Europe's agricultural and technological advances, the rise of China as a sea power, and the rise of new civilizations in the desert regions of the Americas.